The Role of Work Motivation in Mediating Work Discipline and Work Culture on Employee Performance - Ida Ayu Oka Martini; I Wayan Gde Sarmawa; Desak Made Febri Purnama Sari (Universitas Warmadewa, 2024)
Work dicipline and work culture are based variable that can affect employee performance. The purpose of this research is to analyze (1) the effect of work discipline and work culture on employee performance; and (2) the role of work motivation in mediating work discipline and work culture on employee performance. Research conducted at PT. Multi Jaya Agung in Denpasar City, Bali Province. The number of research samples is 50 respondents. Respondents in this study were 50 employees. Data analysis using the smartPLS 3.2.8 program. The results showed that Work Discipline had a not significant positive effect on employee performance, work discipline had a positive and significant effect on work motivation, work motivation had a positive but not significant effect on employee performance, work culture had a positive and significant effect on employee performance, work culture had a positive effect and significant effect on work motivation, work motivation does not mediate work discipline on employee performance, and work motivation does not mediate work culture on employee performance.